Is there an alternative to the indirect immunofluorescence ANA HEp-2 assay for the diagnosis of connective tissue diseases? - Hadjout, Tamazouzt; Lamara Mahammed, Lydia; Saad, Meriem; Zemmour, Amel; Tamechmacht, Nadia; Bousbia, Ghalya; Ismail, Halima; Dahmani, Nawel; Allam, Ines; Djidjik, Reda (Frontiers in Immunology, 2025)
BackgroundAnti-nuclear antibodies (ANA) are serological hallmarks in the diagnosis of ANA-associated rheumatic diseases (AARD). For many years, indirect immunofluorescence (IIF) on HEp-2 cell substrate has been regarded as the gold standard method for ANA detection. Nowadays, several solid phase immunoassays (SPA) have been developed for ANA screening. The aim of this study was to evaluate three automated assays as potential alternatives to the IIF HEp-2 assay for ANA detection in the diagnosis of AARD.Patients and methodsThis study included 271 patients referred to our department for routine ANA testing: 94 patients with confirmed AARD, 144 in whom AARD was excluded and 33 with an uncertain AARD diagnosis. For all sera, ANA detection was initially performed using an IIF HEp-2 assay (EUROIMMUN®, Lubeck, Germany), then assessed by two chemiluminescence immunoassays (CLIAs) on the MAGLUMI® X3 (Snibe, Shenzhen, China) and the iFlash 1800® (YHLO, Shenzhen, China), and an automated enzyme immunoassay (EIA) UNI® (NeoMedica, Nis, Serbia). For identification, we performed anti-ENA and anti-DNA assays using the CLIA MAGLUMI® X3 or the ELISA EUROIMMUN® assay.ResultsThe highest positivity rate was found with the MAGLUMI in the AARD group, with the highest concordance rate with IIF (77.9% vs. 73.4% with UNI, and 71.2% with iFlash). The three automated ANA assays showed weak agreement with the IIF assay (0.454 ≤ ĸ ≤ 0.551). The three ANA assays showed excellent performance in discriminating between AARD and non-AARD cases (AUC>0.9 for each system). At the manufacturer’s cut-off values, the MAGLUMI assay showed the highest sensitivity (95.7%), and the highest specificity was found with the iFlash (94.4%). Only the MAGLUMI assay showed a negative likelihood ratio <0.1, whereas the UNI and the iFlash ANA assays showed a high positive likelihood ratio (≥10).ConclusionThese findings suggest that SPA can serve as a complementary approach to IIF for ANA screening in the diagnosis of AARD. The MAGLUMI assay could be used for initial screening alongside IIF, depending on the clinical context. A proper adjustment of the threshold of the MAGLUMI ANA Screen assay may improve its specificity and limit false positive results.